Linguistics Relativity: Edward Sapir’s Perspective on Language, Culture, and Cognition - Ronald Maraden Parlindungan Silalahi (Journal of English Language and Culture, 2017)
Language is a sign system which is used by society to cooperate, interact, and identify. Culture, Society, and Cognition is built based on human perception in their world. It is reflected through linguistics element used by language users for communication purposes. The idea about inter-relation of language and those three elements (Culture, Society, and Cognition) is conducted by an anthropologist and linguist, Edward Sapir. Sapir’s perspective on culture is highly influenced by some western linguist and philosopher (like Boas, Morris, and Saussure). Sapir believes that language is cultural product.    The linguistic constructions in particular language are built from influence mechanisms. Each language related to immeasurable variety of experiences and a limited array of formal categories (both lexical and grammatical). These categories coherently related to the interpretation of experience in the world. Whorf believes that the system of categories in each language provides an unusual system to certain language.  Together with Whorf, Sapir conducted a hypothesis. The hypothesis conducted is an idea of differentiating the way of language is encoded cognition category and culture. Their existence in society influences the way of thinking. It influences human thought and action. Language determines thought and linguistics category determine cognitive category. Hypothesis which was conducted by them is named Sapir-Whorf Hypothesis. Keywords: Edward Sapir, Relativity, Culture, Society, Cognition